MDM2 and MDMX promote ferroptosis by PPARα-mediated lipid remodeling - Venkatesh, Divya; O'Brien, Nicholas A; Zandkarimi, Fereshteh; Tong, David R; Stokes, Michael E; Dunn, Denise E; Kengmana, Everett S; Aron, Allegra T; Klein, Alyssa M; Csuka, Joleen M; Moon, Sung-Hwan; Conrad, Marcus; et al. (Genes & development, 2020)
MDM2 and MDMX, negative regulators of the tumor suppressor p53, can work separately and as a heteromeric complex to restrain p53's functions. MDM2 also has pro-oncogenic roles in cells, tissues, and animals that are independent of p53. There is less information available about p53-independent roles of MDMX or the MDM2-MDMX complex. We found that MDM2 and MDMX facilitate ferroptosis in cells with or without p53. Using small molecules, RNA interference reagents, and mutant forms of MDMX, we found that MDM2 and MDMX, likely working in part as a complex, normally facilitate ferroptotic death. We observed that MDM2 and MDMX alter the lipid profile of cells to favor ferroptosis. Inhibition of MDM2 or MDMX leads to increased levels of FSP1 protein and a consequent increase in the levels of coenzyme Q , an endogenous lipophilic antioxidant. This suggests that MDM2 and MDMX normally prevent cells from mounting an adequate defense against lipid peroxidation and thereby promote ferroptosis. Moreover, we found that PPARα activity is essential for MDM2 and MDMX to promote ferroptosis, suggesting that the MDM2-MDMX complex regulates lipids through altering PPARα activity. These findings reveal the complexity of cellular responses to MDM2 and MDMX and suggest that MDM2-MDMX inhibition might be useful for preventing degenerative diseases involving ferroptosis. Furthermore, they suggest that MDM2/MDMX amplification may predict sensitivity of some cancers to ferroptosis inducers.